Connectivity between the Latin American and U.S. stock markets in the presence of the Covid-19 pandemic - Ceretta, Paulo Sergio; Dutra, Vanessa Rabelo; Marschner, Paulo Fernando (Revista de Administração da UFSM, 2022)
Objective - This paper aims to revisit the relationship between the Latin American and U.S. stock markets during the Covid-19 pandemic. Methodology- The dynamic connectivity between these markets was estimated by implementing the time-varying VAR model (TVP-VAR) for daily data from January 2010 to June 2021. Results - There are three main results. First, although spillovers from each market accounted for most of their variance, exchanges were not entirely independent of each other. Second, the U.S. and Brazil were net transmitters of spillovers, while Argentina and Chile were net receivers. Finally, the magnitude of net spillovers is not high enough to characterize a contagion effect. Practical implications - The inclusion of Latin American stock markets in the scope of Covid-19 studies is an important contribution to the literature that often neglects Latin American markets in its samples. Originality - The study of the connection between markets in the presence of Covid-19 differs from most that focus exclusively on the impact of Covid-19. Understanding the relationship between Latin American and U.S. markets in the presence of a crisis unlike any that has occurred before can help investors in their investment strategies and policymakers, governments, and monetary authorities interested in the integration or disintegration between markets.